Strain rate-dependent large deformation inelastic behavior of an epoxy resin. (January 2020) - Tamrakar, Sandeep; Ganesh, Raja; Sockalingam, Subramani; Haque, Bazle Z (Gama); Gillespie, John W
The objective of this paper is to model high strain rate and temperature-dependent response of an epoxy resin (DER 353 and bis( p -aminocyclohexyl) methane (PACM-20)) undergoing large inelastic strains under uniaxial compression. The model is decomposed into two regimes defined by the rate and temperature-dependent yield stress. Prior to yield, the model accounts for viscoelastic behavior. Post yield inelastic response incorporates the effects of strain rate and temperature including thermal softening caused by internal heat generation. The yield stress is dependent on both temperature and strain rate and is described by the Ree–Erying equation. Key experiments over the strain rate range of 0.001–12, 000/s are conducted using an Instron testing machine and a split Hopkinson pressure bar. The effects of temperature (25–120 ℃) on yield stress are studied at low strain rates (0.001–0.1/s). Stress-relaxation tests are also carried out under various applied strain rates and temperatures to obtain characteristic relaxation time and equilibrium stress. The model is in excellent agreement over a wide range of strain rates and temperatures including temperature in the range of the glass transition. Case studies for a wide range of monotonic and varying strain rates and large strains are included to illustrate the capabilities of the model.